ANALYSIS OF THE FINANCIAL PERFORMANCE AND FINANCIAL HEALTH OF PT GUDANG GARAM TBK FOR THE 2021–2023 PERIOD - hamizar Hamizar (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the financial performance and financial health rating of PT Gudang Garam Tbk during the 2021–2023 period by applying financial ratio analysis, including liquidity, solvency, profitability, and activity ratios, as well as the standard ratios stipulated in the Decree of the Minister of State-Owned Enterprises No. KEP-100/MBU/2002. The study uses secondary data obtained from the company’s annual financial statements published by the Indonesia Stock Exchange for 2021–2023. The results show that PT Gudang Garam Tbk remained liquid; however, its liquidity declined each year, particularly in the quick ratio and cash ratio, both of which were below ideal industry standards. In terms of solvency, the debt-to-assets and debt-to-equity ratios remained within reasonable limits, indicating a stable financial structure and a relatively low level of financial risk. Profitability fluctuated, although return on assets (ROA) and net profit margin (NPM) were relatively stable. With respect to activity ratios, the company demonstrated high efficiency in managing receivables, both in collection frequency and the speed of cash collection. Based on its financial health rating, the company was categorized as less healthy throughout the 2021–2023 period.